(untitled) (Research, Society and Development, 2021)
Distance learning in higher education has grown substantially in Brazil, for some it is a modality and for others a new pedagogy with a new field of study, especially in adult education. This boost in Distance Education is marked by the growth in both institutions and students through the expansion of courses and support centers, democratizing education. In this away, one aspect that has been discussed and disputed in distance education is quality. Studies show that there is equivalence in quality between classroom teaching and e-learning when considering the grades of the evaluations for higher education. The aim of this study was to identify which factors are linked to quality in distance education. For this, a bibliographic analysis was performed following selection procedures regarding citation and expert analysis to list the articles to be evaluated. After this filter, the conclusion of these articles was selected and content analysis was applied using the Iramuteq software. The results indicate that quality is a polysemic concept and is related to management, team engagement, faculty, student body, institutional assessments, legislation, infrastructure, management, technologies and their applications.